2014
DOI: 10.1103/physrevlett.112.213602
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Polariton Dynamics in Coupled Highly Dissipative Cavities

Abstract: Coherent light-matter interaction at the single photon and electronic qubit level promises the remarkable potential for nonclassical information processing. Against the efforts of improving the figure of merit of the cavities, here we demonstrate strong anharmonicity in the polariton dressed states via dark state resonances in a highly dissipative cavity. It is shown that vacuum Rabi oscillation occurs for a single quantum emitter inside a cavity even with bosonic decay-to-interaction rate ratio exceeding 10 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 49 publications
2
71
0
Order By: Relevance
“…The linewidths do not show a crossed pattern as in the conventional cavity-QED case [53], because cavity mediated LSPR-emitter coupling poses both dispersive and dissipative nature. The similar mechanism was reported in exciton mediated optomechanical coupling [54] and low-Q cavity mediated cavity-QED coupling [55]. The dispersive coupling leads to the repulsion of eigenfrequencies' real parts [ Fig.…”
Section: (C)supporting
confidence: 56%
“…The linewidths do not show a crossed pattern as in the conventional cavity-QED case [53], because cavity mediated LSPR-emitter coupling poses both dispersive and dissipative nature. The similar mechanism was reported in exciton mediated optomechanical coupling [54] and low-Q cavity mediated cavity-QED coupling [55]. The dispersive coupling leads to the repulsion of eigenfrequencies' real parts [ Fig.…”
Section: (C)supporting
confidence: 56%
“…[15,17], we have demonstrated an enhancement of the dipole+dipole interaction between two atoms trapped in an optical cavity. [14], in particular it allows the primary cavity coupled to quantum emitter to be highly dissipative (i.e., low Q). This scheme contains unique advantages of the coupled cavity configuration proposed in ref.…”
Section: Doi: 101002/andp201900220mentioning
confidence: 99%
“…[12] Such strong interaction often requires resonators with high quality (Q) factor and small mode volume (V ) simultaneously, which is still difficult to engineer in experiments. It is demonstrated that by employing a coupled cavity configuration, [13] the requirement for high Q and small V for one cavity can be removed, [14] hence, effective strong coupling in highly dissipative cavity QED system is realized. It is demonstrated that by employing a coupled cavity configuration, [13] the requirement for high Q and small V for one cavity can be removed, [14] hence, effective strong coupling in highly dissipative cavity QED system is realized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently atomic and semiconductor cavity QED has been extensively studied [19][20][21][22], they present new concepts and new applications for novel optical sources with attractive proprieties [23][24][25][26][27][28] such as chaos [29], antibunching [30], squeezing [31], and entanglement [32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%